2015
DOI: 10.1007/s00428-015-1841-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic nodular lymphoid lesion with increased IgG4-positive plasma cells associated with primary biliary cirrhosis: a report of two cases

Abstract: The nodular lymphoid lesion of the liver known as reactive lymphoid hyperplasia or pseudolymphoma is rare and its pathogenesis is unknown. We report two cases of nodular lymphoid lesions of the liver with numerous IgG4-positive plasma cells in patients with primary biliary cirrhosis. Histologically, in both cases, the lesion showed a dense lymphoplasmacytic infiltrate with lymphoid follicles and granulomas. Fibrous tissue was scarce and without a storiform pattern. Obliterative phlebitis was not identified. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In this case, HPL appeared during the course of PBC, but there were also 13 cases (16.3%) of HPL associated with PBC (Table ) . Because the lesion had been misdiagnosed as HCC or another malignant tumor, 10 HPL patients associated with PBC underwent hepatic resections.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this case, HPL appeared during the course of PBC, but there were also 13 cases (16.3%) of HPL associated with PBC (Table ) . Because the lesion had been misdiagnosed as HCC or another malignant tumor, 10 HPL patients associated with PBC underwent hepatic resections.…”
Section: Discussionmentioning
confidence: 88%
“…Histologically, the interlobular bile ducts are primarily damaged and show characteristic findings, such as chronic nonsuppurative destructive cholangitis (CNSDC), followed by progressive bile duct loss . Some of the HPL patients present with extrahepatic autoimmune diseases, such as Sjogren's syndrome, autoimmune thyroiditis, Takayasu aortitis with antiphospholipid syndrome, or calcinosis, Raynaud's phenomenon, esophageal dysmotility, sclerodactyly, and telangiectasia (CREST syndrome; 13). Because HPL has a relatively large number of autoimmune disease complications, it is suggested that an autoimmune mechanism is involved in the increase in HPL .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some reports have examined the use of FDG-PET in the diagnosis of hepatic pseudolymphoma. We found 9 cases in which FDG-PET was used to examine patients with hepatic pseudolymphoma, including our own (Table 2 ) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Seven (78%) of 9 cases showed FDG uptake in the tumor, and the median SUV max was 4.3 (range: 3.4–7.2).…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative diagnosis of hepatic pseudolymphoma is difficult because noninvasive radiological examinations such as ultrasonography (US), computed tomography (CT), and magnetic resonance imaging are usually equivocal. Recently, some reports have examined the use of fluorodeoxyglucose positron emission tomography (FDG-PET) in the diagnosis of hepatic pseudolymphoma [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. We herein report a case of hepatic pseudolymphoma with FDG uptake on PET and examine the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologically, it is characterized by a marked proliferation of non‐neoplastic polyclonal lymphocytes without atypia and mitosis, in which lymphoid follicles of various sizes and shapes with germinal centers can be detected . Until now, no more than 100 cases have been reported in the English literature . Follow‐up or a conservative strategy should be undertaken instead of surgery if a definite diagnosis is made .…”
mentioning
confidence: 99%